Prevalence of and Risk Factors for Multidrug-Resistant Bacteria in Urine Cultures of Spinal Cord Injury Patients - Kang, Min-Soo (Ann Rehabil Med, 2015)
OBJECTIVE: To identify the prevalence of multidrug-resistant (MDR) bacteria and identify their specific risk factors in routine urine specimens of spinal cord injury (SCI) patients. METHODS: This study was designed in a retrospective manner, reviewing the medical records of SCI patients who were admitted to a specialized SCI unit between January 2001 and December 2013. Patients were investigated for age, gender, American Spinal Injury Association impairment scale, SCI level, duration after injury, bladder management method, and hospitalization history within four weeks prior to visiting our unit. The results of routine urine cultures including presence of MDR organisms were analyzed. RESULTS: Among the total 2,629 urine samples from the newly admitted SCI patients, significant bacteriuria was identified in 1,929 (73.4%), and MDR organisms were isolated in 29 (1.1%) cultures. There was an increasing trend of MDR organism prevalence from 2001 to 2013 (p<0.01). The isolation of MDR organisms in inpatients who were admitted for rehabilitation (1.3%) was significantly higher than it was among community-residing persons (0.2%) (p<0.05). By voiding method, patients who used a suprapubic indwelling catheter (3.3%) or a urethral indwelling catheter (2.6%) showed a higher rate of MDR organism isolation (p<0.05). CONCLUSION: There was an increasing trend of MDR organism isolation in SCI patients. Inpatients and persons who used indwelling catheters showed a higher risk of MDR organism isolation.